2001
DOI: 10.1210/mend.15.10.0705
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Pituitary Adenylate Cyclase-Activating Polypeptide Gene Results in Early Postnatal Death Associated with Dysfunction of Lipid and Carbohydrate Metabolism

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is a hormone belonging to the glucagon superfamily of hormones. These hormones are known to play important roles in metabolism and growth. PACAP is a neuropeptide that causes accumulation of cAMP in a number of tissues and affects the secretion of other hormones, vasodilation, neural and immune functions, as well as the cell cycle. To determine whether PACAP is essential for survival and to evaluate its function(s), we have generated mice lacking the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
107
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 38 publications
5
107
1
1
Order By: Relevance
“…To evaluate the functionality of the VIP receptors expressed in skeletal muscle and to validate the observation that only VPAC2R is expressed in skeletal muscle, skeletal muscles in organ bath were stimulated with either the VPACR-nonselective agonist VIP, the VPAC1R-selective agonist [K 15 ,R (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), or the VPAC2R-selective agonist Ro-25-1553, and cAMP generation was evaluated. As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the functionality of the VIP receptors expressed in skeletal muscle and to validate the observation that only VPAC2R is expressed in skeletal muscle, skeletal muscles in organ bath were stimulated with either the VPACR-nonselective agonist VIP, the VPAC1R-selective agonist [K 15 ,R (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), or the VPAC2R-selective agonist Ro-25-1553, and cAMP generation was evaluated. As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…What then is the function of VPAC2R in skeletal muscle biology? The PACAPreceptor family and associated ligands have been shown to have an important role in energy homeostasis (14). In particular, VPAC2R functions in the pancreas and adipose tissue to control glucose deposition and fat deposition, respectively (44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that PACAP Ϫ/Ϫ mice present numerous phenotypes, including high mortality of PACAP Ϫ/Ϫ mice (37), inadequate heat production (38), reduction in glucose levels (39), and deficits in circadian light response (40). It is possible that these factors could influence testicular aging as well.…”
Section: Discussionmentioning
confidence: 99%
“…24 We conclude that the metabolic decompensation shortly before death is a consequence of severe right heart failure in mice lacking PAC1 and therefore, does not account for a specific primary role of PAC1 in lipid metabolism, as has been proposed for its ligand, in PACAP-deficient mice. 25 Mainly 3 signs, rarefaction of lung capillaries, increased muscularization of small pulmonary vessels, and elevated right ventricular end-systolic pressure, directly pointed out that PAC1-deficient mice suffered from pulmonary hypertension. It is interesting to note that the observed alterations in media thickness (plus 65% in mutant mice) and right ventricular end-systolic pressure (plus 45% in mutant mice) in PAC1 mutants are identical to those seen in other murine models of pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%